New perspectives on the planning of Yuan Dadu: The Yuan measurement system, residential space and nomadic life - Zhao, Chunxiao (International Planning History Society Proceedings, 2018)
Recent studies on Dadu, one of the capital cities of the Mongol Yuan dynasty, were increasingly situated in a holistic Eurasian background, shedding new light on the influence of nomadic traditions in its city planning in addition to using Chinese urban models. Whereas most of the previous studies took physical remains as their point of departure, this paper aims to understand the nomadic characteristics of Yuan Dadu through elucidating its two fundamental yet under-studied planning features: Firstly, the planning of the city in accordance with the unique measurement system of Yuan chi, whose length is significantly different from the Chinese dynasties that ruled from the Central Plains; Secondly, the prescribed eight-mu plot for each household in the History of the Yuan Dynasty, which took the shape of a 32-by-60-step rectangle based on the space model of nomadic families. I argue that the above two points can provide new perspectives on the systematic influence of nomadic way of life seen in the planning of the Yuan Dadu as well as the planning principle established by the Mongol regime.